The clinical significance of allergen-specific IgG4 in allergic diseases - Qin, Lu; Tang, Lan-Fang; Cheng, Lei; Wang, Hui-Ying (Frontiers in Immunology, 2022)
IgG4 is a subclass of IgG antibody with a unique molecular feature of (Fragment antigen- binding) Fab-arm exchange, allowing bispecific antigen binding in a mono-valent manner. With low binding affinity to C1q and Fcγreceptors, IgG4 is incapable of forming immune complexes and activating the complement pathway, exhibiting a non-inflammatory feature. IgG4 is produced similarly to IgE and is considered a modified reaction to IgE class-switching response under certain conditions. It could also counteract IgE-activated inflammation. However, the clinical significance of IgG4 in allergic diseases is complex and controversial. Three viewpoints have been suggested to describe the role of IgG4. IgG4 can act as a tolerance–inducer to play a protective role under repeated and rapid incremental dosing of allergen exposure in allergen immunotherapy (AIT), supported by allergies in cat raisers and venom desensitization in beekeepers. Another viewpoint accepted by mainstream specialists and guidelines of Food Allergy and Management in different countries points out that food-specific IgG4 is a bystander in food allergy and should not be used as a diagnostic tool in clinical work. However, eosinophilic esophagitis (EoE) investigation revealed a direct clinical relevance between physiopathology and serum IgG4 in cow milk and wheat. These factors indicate that allergen-specific IgG4 plays a multifaceted role in allergic diseases that is protective or pathogenic depending on different allergens or exposure conditions.